Growth performance and changes in the leaf metabolite profile of Moringa oleifera Lam. cultivars grown in an open hydroponic system and harvested at different Frequencies - Du Toit, Elsie Sophia (University of Pretoria, 2022)
Thesis (PhD (Horticultural Science))--University of Pretoria, 2022.